UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA KANTONG BILANGAN PADA SISWA KELAS 2 SDIT NURUL ‘ILMI JAMBI - Astuti Hidayati; Indryani; Akhamd Habibi; Ugi Nugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the student learning outcomes in mathematics by using learning media of number pockets for the 2st Secon students of Nurul ‘Ilmi Elementary School in Jambi  regency.  This research was a classroom action research, using the Kemmis and McTaggart models which include planning, action and observation, as well as reflections on each cycle. The subject of this research were the 2st Secon students of Nurul ‘Ilmi Elementary School in Jambi  regency  which amounted to 27 students. Data collection techniques using observation, tests, and documentation. Data is analyzed quantitatively and qualitative. Indicator of success this research was ≥75% of students have reached the KKM, which is 70. The results showed that the media implementation of the number pockets on the mathematics subjects could improve the learning outcomes of the 2st Secon students of Nurul ‘Ilmi Elementary School in Jambi  regency. When it has not been given the value of mathematics teaching the 2st Secon students of Nurul ‘Ilmi Elementary School in Jambi  regency only 11 (40.74%) Students who have a value above the KKM. In the activity of cycle action I increased, namely as much as 15 (55.56%) Students who achieve complete value. And in cycle II as much as 23 (85.19%) Achieve a value of submission. The average value of learning outcomes of cycle I and cycle II has also increased from 62.94 to 82.96.